Generalized anxiety disorder and academic stress in university students during the COVID-19 pandemic. - Izurieta-Brito, Daniel (2022)
The health crisis caused by the Coronavirus Disease 2019 o COVID-19 pandemic, increases its contagiousness, and leaves millions of deaths, as well as significant consequences in the psychic sphere of affected people. Lockdown, mandatory quarantine, and the actions taken to reduce the number of infections lead to negative consequences for the mental health of university students. Objective: To identify the relationship between academic stress and generalized anxiety disorder caused by the COVID-2019 pandemic. Material and Methods: Descriptive-correlational study, using the Cognitive Systemic Inventory of Academic Stress (CSIAS) and the Scale for Generalized Anxiety Disorder (GAD-7), applied to 359 university students of Ecuador during the period May-June 2020. Results: From the total sample, 64.9% were women and 35.1%, men, with 43.7% in the 21-23 years-old group. In the CSIAS, the mean stress was higher in women (X = 3.4313) than in men (X = 3.2142), both groups presenting high levels of academic stress. On GAD-7, 51.5% of women presented symptoms of severe anxiety vs. 34.5% of men. A moderate positive correlation between academic stress and generalized anxiety was shown by a rho = 0.638. Conclusions: There are elevated levels of academic stress among university students, with women as the most affected group. A majority of probands of both genders showed symptoms of severe anxiety.